Research Progress on the Twisted Partially Coherent Beams - WANG Haiyun; LIU Lin; CAI Yangjian (Nantong Daxue xuebao. Ziran kexue ban)
Under the action of twist phase, partially coherent beams display their unique advantages in many applications fields, such as beam shaping, particle trapping, optical imaging, free-space communications, and so on. In this study, a review on the fundamental theory and the development history of twisted partially coherent beams is summarized. Then the theoretical models, propagation characteristics, experimental generation, and related applications of such beams are mainly introduced. And the factors which constrain the development of the beams′ application have been expounded and the future key research subjects have been put forward.